Into the wild [videorecording (DVD)] - Penn, Sean, 1960-; Hirsch, Emile, 1985-; Harden, Marcia Gay; Hurt, William; Krakauer, Jon (Paramount Home Entertainment, 2008)
Freshly graduated from college with a promising future ahead, Christopher McCandless instead walked out of his privileged life and into the wild in search of adventure. What happened to him on the way transformed this young wanderer into an enduring symbol for countless people - a fearless risk-taker who wrestled with the precarious balance between man and nature. Based on a true story.